2022
DOI: 10.1111/apps.12386
|View full text |Cite
|
Sign up to set email alerts
|

Using robots at work during the COVID‐19 crisis evokes passion decay: Evidence from field and experimental studies

Abstract: The growing trend of introducing robots into employees' work lives has become increasingly salient during the global COVID‐19 pandemic. In light of this pandemic, it is likely that organisational decision‐makers are seeing value in coupling employees with robots for both efficiency‐ and health‐related reasons. An unintended consequence of this coupling, however, may be an increased level of work routinisation and standardisation. We draw primarily from the model of passion decay from the relationship and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 124 publications
(186 reference statements)
1
10
0
Order By: Relevance
“…In so doing, we show employees with higher levels of anxious attachment are more sensitive to the experience of interacting with AI, which heightens subsequent feelings of both need for affiliation as well as loneliness. While we generally find support for our hypotheses across the four studies, it is important to be mindful of these findings when considering the implications of our findings for the future of human–AI integration in organizations worldwide (Murray et al, 2021; Tang, Koopman, Elfenbein, et al, 2022; Wilson & Daugherty, 2018), as well as research on affiliation and attachment.…”
Section: Discussionsupporting
confidence: 53%
“…In so doing, we show employees with higher levels of anxious attachment are more sensitive to the experience of interacting with AI, which heightens subsequent feelings of both need for affiliation as well as loneliness. While we generally find support for our hypotheses across the four studies, it is important to be mindful of these findings when considering the implications of our findings for the future of human–AI integration in organizations worldwide (Murray et al, 2021; Tang, Koopman, Elfenbein, et al, 2022; Wilson & Daugherty, 2018), as well as research on affiliation and attachment.…”
Section: Discussionsupporting
confidence: 53%
“…In subsequent quantitative survey research, the authors also found that higher trait levels of self‐control were positively related to current job performance, beyond situational demands and prior performance, and that out of all self‐control strategies investigated earlier, altering somatic conditions (e.g., through taking substances such as coffee or changing one's physical state by dressing up for work) and fostering autonomous motivation (e.g., by reminding oneself of the relevance and importance of the task at hand) were positively related to job performance and mediated the self‐control‐performance relationship. Finally, Tang et al (2022) examined how athletes' (table tennis players) increased interaction with robots during the pandemic crisis in their daily work (training) led to a decrease in passion for their work, which resulted in withdrawal behavior in both the work and family‐related life domains. Finally, they also found that athletes' openness to experience reduced the negative effects of working with robots, indicating the beneficial role of some individual differences in alleviating negative outcomes during the crisis beyond those identified in our review of the existing literature on COVID‐19‐related research, above.…”
Section: Current Contributions Of the Special Issuementioning
confidence: 99%
“…Passion is necessary for success in settings where heightened levels of personal attachment exist (McAllister et al. , 2017; Tang et al. , 2022).…”
mentioning
confidence: 99%
“…Research suggests that technology infusions hastened a level of employee “passion decay” that affected work and home domains. Tang et al. (2022) found that working closely with automated technology and the associated routinization predicted passion decay.…”
mentioning
confidence: 99%
See 1 more Smart Citation